Many losers and a few winners: polymorphic life-history of non-native largemouth bass is explained by ontogenetic diet shift and prey growth rate - Ishikawa, Tetsuroh; Kida, Kohta; Kashiwagi, Yoshihiro; Tachihara, Katsunori (Ichthyological research, 2023)
Invasion biologists have attempted to reveal intraspecific variability of biological traits of non-native species at large spatial scales, but the knowledge of the intraspecific variability of invasive species within a single population (such as resource polymorphism) is still limited. In this study, we report the intraspecific variability in life-history traits of a non-native largemouth bass (LMB) population in a subtropical reservoir and discuss the causes and mechanisms of this novel resource polymorphism in relation to ontogenetic diet shift (ODS) and growth rate of prey fish. A polymorphic LMB population was characterized as the sympatric occurrence of “normal” and “dwarf” forms. The normal form showed evident ODS in their diet from smaller gobies to larger prey such as bluegill (BG). In contrast, the majority of dwarfs preyed on gobies throughout their life, because the BG population rapidly grew out of the predation window of dwarfs under the subtropical warm climate. Analysis of the first-year life-history of LMB suggested that the shift of individuals to normal form is irreversibly determined by first-year growth and that the largest size class of the young-of-the-year cohort reaching 180–200 mm standard length and experiencing ODS can shift to the normal form. In conclusion, scarcity of alternative prey and rapid escape of BG from the predation window prevents ODS in dwarfs, creating distinct resource use patterns and diverging life-history traits between the two forms. Novel resource polymorphism in LMB is likely a response to food limitation, and whether this response is based on phenotypic or genetic plasticity should be clarified.